Probiotics your friendly gut bacteria - Abd. Manap, Mohd. Yazid (Penerbit Universiti Putra Malaysia, 2008)
The functional food concept has in recent years, moved progressively towards the development of dietary supplements that may stimulate gut microbial composition and activities. The rationale behind these advances is consequent to the realization that gut microflora has profound influence on the host’s health. The human gastrointestinal tract (GIT) represents an ecosystem of the highest complexity and is very dynamic in composition. The micro biota exists in a commensal, symbiotic or an antagonist microbial relationship. Among more than 400 species of bacteria present in the GIT of an adult human being, bifidobacteria and lactobacillus are considered to be the most beneficial to human health. Members of these genera are thought to enhance digestion, adsorption of nutrients, prevention of colonization by pathogens, decreasing serum cholesterol and stimulation of immune responses. The ability of these bifidobacteria and lactobacilli to ferment non-digestible oligosaccharides may be an important characteristic which enables them to establish themselves in the colon. Studies were undertaken by researchers in our laboratory to elucidate the probiotic characteristics and effects of the bifidobacteria species isolated from the human GIT and to propose screening, cultivation and preservation and delivery techniques for this bacterium.